Teores e estoque de carbono em frações lábeis e recalcitrantes da matéria orgânica do solo sob integração lavoura-pecuária no bioma Cerrado - Batista, Itaynara [UNESP]; Pereira, Marcos Gervasio; Fernandes Correia, Maria Elizabeth; Bieluczyk, Wanderlei; Schiavo, Jolimar Antonio; Costa Rows, Janaina Ribeiro (Universidade Estadual de Londrina (UEL), 2013)
The study of organic matter and its compartments and their relationship with management, aims to develop strategies for increasing their levels in soils and better understanding of its dynamics. This work aimed to evaluate the fractions of soil organic matter and their carbon stocks in different soil cover system in crop-livestock integration and native Cerrado vegetation. The study was conducted at the farm Cabeceira, Maracaju-MS, sample area have the following history: soybean/corn + brachiaria/cotton/oat + pasture/soybean/formation of pasture/grazing, sampling was carried out in two seasons, dry (May/2009) and rainy (March 2010), in the dry season, crops present were: pasture, corn and cotton + brachiaria and in the rainy season were corn, cotton and soybeans, so the areas in the two evaluation periods were: pasture / maize + brachiaria / cotton, cotton / soybean area and a native of Savanna. Was performed to determine the exchangeable cations, particle size analysis, bulk density, organic carbon, particle size fractionation of organic matter of the soil with the quantification of particulate organic carbon (POC) and organic carbon associated with minerals (OCam). Was also quantified the carbon stock and size fractions. The area of pasture / maize showed higher carbon stock in the particulate fraction in the topsoil. The area of cotton / soy due to its lower clay, showed the greatest loss of carbon. Because of the areas have the same history, the stock of more recalcitrant fraction was not sensitive to variations in coverage. The POC fraction appears more sensitive to different soil covers and seasonality.
Content and carbon stocks in labile and recalcitrant organic matter of the soil under crop-livestock integration in Cerrado
Keywords: Particle size fractionation; seasonality; management